2001
DOI: 10.1097/00003246-200110000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Infusion of methylene blue in human septic shock: A pilot, randomized, controlled study

Abstract: In human septic shock, continuously infused MB counteracts myocardial depression, maintains oxygen transport, and reduces concurrent adrenergic support. Infusion of MB appears to have no significant adverse effects on the selected organ function variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
179
4
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(191 citation statements)
references
References 36 publications
4
179
4
4
Order By: Relevance
“…When compared to the control group, methylene blue reduced pressor requirement. Although 5/10 patients treated with methylene blue survived as opposed to 3/10 patients who received conventional treatment, this study was not powered to find a mortality difference [83].…”
Section: The No-cgmp Pathway In Anaphylaxis and The Role Of Methylenementioning
confidence: 92%
“…When compared to the control group, methylene blue reduced pressor requirement. Although 5/10 patients treated with methylene blue survived as opposed to 3/10 patients who received conventional treatment, this study was not powered to find a mortality difference [83].…”
Section: The No-cgmp Pathway In Anaphylaxis and The Role Of Methylenementioning
confidence: 92%
“…In this case, we report the need for a prolonged infusion of MB over a period of 120 hr in a patient with intractable septic shock. Previous research has demonstrated that MB may be efficacious in septic shock when given by intravenous bolus or short-term (B6 h) infusions, 3,4,9,11,[16][17][18] although a case report of a longer-term infusion of 44 hr has been described. 12 Despite standard treatment for septic shock with early goal-directed therapy, conventional vasopressors, including norepinephrine, epinephrine, and vasopressin, our patient responded only to the administration of MB.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12] Little is known about the clinical utility, optimal dose, or duration of MB administration in patients with septic shock. The relatively few reports available on the use of MB in septic shock describe relatively short infusions.…”
Section: Résumémentioning
confidence: 99%
See 1 more Smart Citation
“…Dose-related neurotoxicity of MB affecting the central nervous system with higher doses (between 5 mg/kg and 50 mg/kg) than those used in the present study, as well as possible interspecies differences [97,100], have been described. The clinical efficacy and safety of MB are well documented with both intermittent [189,190] and continuous administration [91]. Further, the cost-effectiveness ratio of MB could be more advantageous than for the newer compounds with inhibitory effect on NOS.…”
Section: The Dose Of Methylene Bluementioning
confidence: 99%